Gestión por procesos y calidad del servicio en funcionarios de la defensoría del pueblo - Loreto 2023 - Cambunungui Perez, Jessica (2024)
The objective of the study was to know if process management and service quality are related. To collect the two data, the survey and the process management and service quality scale were used. The sample was made up of 70 workers from the ombudsman's office. The findings showed that process management and Service quality have a moderate negative relationship ( 0.050) and that adding its significance to (0.678), which means that the Ha cannot be rejected. These findings provide valuable information on the perception of employees, but the lack of statistical significance indicates that there is no strong evidence of a significant correlation between these variables.